ANALYSIS OF OPPORTUNITIES TO INCREASE THE EXPORT VOLUME OF TOURISM SERVICES IN UZBEKISTAN (Marketing Jurnali, 2024)
Tourism plays a significant role in the global economy, particularly for developing countries seeking to diversify their economic base. Uzbekistan, with its rich cultural heritage and strategic location, is positioned to capitalize on the growing global demand for tourism services. This paper examines the opportunities to increase the export volume of tourism services in Uzbekistan by identifying key determinants, barriers, and growth potentials. Employing an econometric analysis using data from 2000-to 2023, this study explores the relationship between tourism exports and several economic and policy variables. The findings suggest that investment in infrastructure, government reforms, and targeted marketing can significantly increase Uzbekistan’s tourism export potential.